2021
DOI: 10.1093/cid/ciab234
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection Rates Among Patients Who Previously Tested Positive for Coronavirus Disease 2019: A Retrospective Cohort Study

Abstract: Background Protection afforded from prior disease among patients with coronavirus disease 2019 (COVID-19) infection is unknown. If infection provides substantial long-lasting immunity, it may be appropriate to reconsider vaccination distribution plans. Methods This retrospective cohort study of one multi-hospital health system included 150,325 patients tested for COVID-19 infection via PCR from March 12, 2020 to August 30, 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
125
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(137 citation statements)
references
References 15 publications
(14 reference statements)
8
125
4
Order By: Relevance
“…It is reasonable to expect that immunity acquired by natural infection provides effective protection against future infection with SARS-CoV-2. Observational studies have indeed found very low rates of reinfection over the following months among survivors of COVID-19 [6][7][8]. Reports of true reinfections are extremely rare in the absence of emergence of new variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to expect that immunity acquired by natural infection provides effective protection against future infection with SARS-CoV-2. Observational studies have indeed found very low rates of reinfection over the following months among survivors of COVID-19 [6][7][8]. Reports of true reinfections are extremely rare in the absence of emergence of new variants.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have found very low rates of reinfection among individuals with prior SARS-CoV-2 infection [6][7][8]. This brings up the question about whether it is necessary to vaccinate previously infected individuals.…”
mentioning
confidence: 99%
“…The total cumulative rate as of December 2020 was~13%, and this background rate of past infectivity will factor into the goal of achieving herd immunity in conjunction with the national vaccination program [17,18]. Indeed, tracking of 150,000 previously infected individuals in Ohio and Florida from March 2020 to August 2020 showed that these individuals were relatively protected from re-infection, like vaccination [6]. In the current study the highest rates of past infection were observed in donors under 30 years of age, and more generally on the West side of the GCMA compared to the East side and adjoining regions of Kentucky.…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration in achieving herd immunity is quantifying background rates of previous infection within the population [4]. In general, previously infected individuals are resistant to new infection for a period, and/or they appear to have a reduced severity of disease if reinfected [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the NAb detection was not implemented in this study. 27 Therefore, till date, the protective level of NAb titers in humans has not yet been identified. In an animal study in ferrets, direct-contact transmission was observed only from reinfected ferrets with low NAb titers (<20).…”
Section: Discussionmentioning
confidence: 99%